Pelatihan Mendongeng Untuk Peningkatan Kualitas Pengajaran Bahasa Indonesia Bagi Guru SD di Kabupaten Soppeng - Nojeng, Asis; Asri Ismail; Abdul Haliq; Faisal; Fiddienika, Arief (Jurusan Pendidikan Teknik Elektro, 2024)
This activity aims to enhance the storytelling skills of Indonesian language teachers at the elementary school level in Soppeng through a structured approach that focuses on the real needs of educators. The program is implemented in four essential stages: first, a training needs analysis is conducted to identify the challenges and opportunities faced by teachers in implementing storytelling techniques; second, the development of relevant and engaging training materials tailored to the characteristics of students and the learning context in elementary schools; third, the execution of training that includes both theoretical and practical sessions, providing opportunities for teachers to practice and directly apply storytelling techniques; and lastly, an evaluation of the activities to assess the effectiveness of the training and to establish steps for future improvements. The results of the evaluations conducted during and after the training implementation indicate a significant increase in the understanding and storytelling skills of the teachers. Through this enhancement, the teachers are not only able to tell stories more engagingly but also integrate storytelling techniques into the Indonesian language learning process in the classroom. Improved storytelling skills are expected to stimulate students' reading interest and literacy, as well as create a more interactive and enjoyable learning experience. Consequently, this activity not only provides a positive impact on the professional development of teachers but also contributes to the growth of more innovative and effective Indonesian language education at the elementary school level. Further research is still needed to explore the long-term impacts of this training and how storytelling techniques can be further optimized within the educational context. Keywords: storytelling, Indonesian language teaching, training.